The impact of physical activity on the risk and severity of COVID-19 infection - Aleksandra Kujawa; Urszula Matuszewska; Aleksandra Nykowska; Katarzyna Beutler; Bartosz Bijata; Dawid Burek; Aleksandra Paszkowska (Kazimierz Wielki University, 2024)
Introduction: A rapid outbreak of SARS-CoV-2 in the past few years caused a significant increase in the number of upper respiratory tract infections throughout the world. Numerous public health institutions tried to control the COVID-19 pandemic, including mandatory mask wearing, vaccinations, increased frequency of using disinfectants or compulsory lockdowns. Lockdown interventions were necessary, although they lead to insufficient, comparing to the international recommendations, levels of physical activity, which could trigger an elevated susceptibility to diseases of affluence. Purpose: Regular aerobic exercise may suppress inflammation, boost innate immunity and result in enhanced protection against viral infections. This review aims to show the relationship between level of physical activity and the risk and severity of COVID-19 infection